Faktor Yang Mempengaruhi Keputusan Konsumen Terhadap Pembelian Sayur Hortikultura di Pasar Tradisional Bangsalsari - Dewi, Layli Rizka; Yasin, Mochammad (KUBIS, 2023)
Development in agriculture, especially the food crops and horticulture sub-sector, currently has a very important role for the community in fulfilling food and nutrition as well as increasing people's income and welfare. The aims of the research are to find out what factors influence consumer decisions to purchase horticultural vegetables and to find out what factors are most dominant in influencing consumer decisions to purchase horticultural vegetables The selection of the research location was carried out intentionally or through purposive sampling. The researcher determined 50 people as respondents who were taken deliberately and who were suitable as data sources. The data collection method uses primary and secondary data obtained from agencies such as market offices, village offices and other relevant literature.The results showed that it was known that internal factors had a dominant influence on consumer decisions in purchasing horticultural vegetables, factors that most dominantly influenced consumer decisions in purchasing horticultural vegetables were habit factors